2013
DOI: 10.1002/asi.22917
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric mapping of the structure of STEM education using co‐word analysis

Abstract: STEM, a set of fields that includes science, technology, engineering, and mathematics; allied disciplines ranging from environmental, agricultural, and earth sciences to life science and computer science; and education and training in these fields, is clearly at the top of the list of priority funding areas for governments, including the United States government. The U.S. has 11 federal agencies dedicated to supporting programs and providing funding for research and curriculum development. The domain of STEM e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 42 publications
2
44
0
7
Order By: Relevance
“…In addition to the inventory work by Assefa and Rorissa (2013) and Adualrob and Daniel (2013), the current study contributes to the field as it presents a typology for term analysis and subsequent findings within a terminology inventory. The findings indicate that there are numerous places where common terminology is aligned and used similarly both across grade bands and between the sets of standards.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition to the inventory work by Assefa and Rorissa (2013) and Adualrob and Daniel (2013), the current study contributes to the field as it presents a typology for term analysis and subsequent findings within a terminology inventory. The findings indicate that there are numerous places where common terminology is aligned and used similarly both across grade bands and between the sets of standards.…”
Section: Discussionmentioning
confidence: 94%
“…Thus the amalgamation of the STEM fields under a singular umbrella poses a threat of failing to honor each discipline's distinctness. Assefa and Rorissa (2013) suggest that " [u]nderstanding the complex web of relationships surrounding the field of STEM education is the first step to better planning of curricular activities, programs, and research" (p. 2514). Chiu et al (2015), in their literature review of the support for STEM in younger grades, reported that little research in general exists on elementary and middle school STEM education and pedagogy.…”
Section: Stem Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Técnicamente son objetos multi-semióticos caracterizados por el hecho de que las relaciones entre los signos y los símbolos están ordenados por medidas que redireccionan a códigos específicos (Lancia, 2012), por lo que posibilitan realizar inferencias sobre las relaciones que organizan las formas del contenido, debido a que las relaciones de las formas de expresión no son casuales, sino que están constituidas por las medidas y algoritmos que determinan la organización de los espacios semánticos multidimensionales (Lancia, 2007). Su uso se extiende desde el análisis de la literatura científica y técnica para representar los conocimientos sobre áreas temáticas determinadas (Balzano et al, 2009;Capone y Petrillo, 2011;Kirkels, 2012), incluyendo estudios de co-palabras sobre educación (Assefa y Rorissa, 2013), hasta las formas que adquieren el discurso, las representaciones sociales y prácticas reflexivas en diversos grupos humanos (Benavente y Cortini, 2010;Bruno, Galuppo y Gilardi, 2011; De Rosa y Holman, 2011) y en la web social (Veltri, 2013).…”
unclassified